A Study of the Islamic Strategies for Prevention and Management of Pandemic Diseases (COVID-19) - Kamal-deen Sulaiman (AlQalam Journal of Medical and Applied Sciences, 2020)
Islam is the religion of all ages. It is adaptive, assimilative and accommodating religion that provides its adherents an unparalleled blueprint to lead an exemplary life. It guides its followers about every aspect of life, be it of past, present and future. Therefore, a true believer always looks towards Islam whenever he encounters any calamity or catastrophe. The latest outbreak of COVID-19 also warrants moving towards Islamic teachings for coping strategies. Corona virus, for sure, is an apocalypse for humanity. The aim of this article therefore, is to analyze the guidelines that Islam provides to its followers, for prevention and management of the pandemic. The paper reveals that, what today immunologists and the WHO are suggesting as preventive measures in order to remain protected from global contagion, were also advised by Prophet Muhammad (SAW) about 1500 years back. In addition to these, Islam recommended seeking medical treatment, intake of good foods and drinks, supplications/Dua and submission to the will of Allah (Pre-destination).The paper observes that, it is incredible to think that, about 1,500 years ago, a Prophet with no scientific training already knew, step by step, what to do during a pandemic that are still applicable in this 21st century. It concludes that, both preservation of the religion and preservation of life are amongst the primary objectives of the Sharīʿah.